HIV-1 infects macrophages by exploiting an endocytic route dependent on dynamin, Rac1 and Pak1. - Carter, G; Bernstone, L; Baskaran, D; James, W (2011)
Recent studies provide compelling evidence that HIV-1 entry in cell lines and lymphocytes proceeds by endocytosis, but these studies are still lacking in macrophages, an important natural target cell for HIV-1. Macrophages exhibit continual and extensive endocytic activity as part of their natural functions, so we investigated the uptake pathways involved in productive HIV-1 entry. We find that caveolae are not utilised by HIV-1, because the main structural proteins, caveolin-1 and 2 are absent from most human leukocytes. We then focused on macropinocytosis; we find that HIV-1 entry into macrophages is sensitive to inhibitors of Na(+)/H(+) exchange, actin rearrangement, dynamin, Rho family GTPases, and Pak1, but not to inhibitors of PI-3 kinase and myosin II. This leads us to conclude that HIV entry into macrophages proceeds by an endocytic pathway that is not classical macropinocytosis. Because of the limitations of a purely pharmacological study such as this, the final elucidation of this pathway awaits the development of reliable forward genetic approaches in authentic macrophages.